Promoting Family-Centered Care in the NICU Through a Parent-to-Parent Manager Position. (April 2015) - Voos, Kristin C.; Miller, Laura; Park, Nesha; Olsen, Steven; Ahern, Kathy
<x xml:space="preserve">Abstract</x> Background: The Family-Centered Care (FCC) committee had formulated multiple ideas for projects but was unable to fully carry out and sustain many of the initiatives. The committee felt that to implement the proposed FCC projects someone would need to devote full attention to the task. The parent-to-parent (PTP) position was created to develop and sustain initiatives of our institution's NICU Family Support Program. Purpose: The purpose of this article is to describe the process of creating a PTP manager position and the effects it can have in the NICU for the family. Program outcomes were assessed in 3 areas that align with core principles of FCC: (1) emotional support and parent empowerment, (2) a welcoming environment with supportive policies, and (3) education for staff and families. The assessment of the program included review and attendance of parent support offerings, review and revision of parent material, and survey evaluation of staff education. Findings/Results: In the first year, the program reached over 800 families, provided 136 parent education hours, and organized social activities that reached 847 families. Implications for Practice: The creation of a PTP manager position has been instrumental in the development and management of multiple initiatives to offer families and staff continued support and education. Implications for Research: Further evaluation of programs and strategies for PTP support in the NICU setting is needed.